Pengembangan E-Modul Pendidikan Agama Islam Dengan Smart Apps Creator Berbasis Pendekatan Game Method Di SMK Muhammadiyah 1 Kalirejo - Diani, Eva Riantika; Ulya , Inarotul; Riskia, Anisa (An Naba, 2025)
This research aims to develop an Islamic Religious Education (PAI) E-Module based on the Game Method approach using the Smart Apps Creator (SAC) application for Muamalah (Mutual Assistance) material at SMK Muhammadiyah 1 Kalirejo. This development was motivated by low student enthusiasm for the PAI learning process, which was considered boring and less interactive. This study employed the Borg & Gall Research and Development (R&D) model (modified) with seven stages. Data collection instruments included validation by material and media experts, teacher assessments, and student response questionnaires. The validation results obtained an average feasibility score of "very feasible" (91%), while student responses to the module's attractiveness averaged 90%, categorized as "very interesting." This indicates that the developed e-module is feasible and interesting for use in PAI learning.